Identify Customer Involvement During Organic Food Purchase Through FCB Grid. Issue 3 (3rd July 2019) - Ghosh, Sanjukta; Barai, Parama; Datta, Biplab
Abstract: The study measures the level of customer involvement related to Organic Food (OF) purchase through FCB Grid. A conceptual model was developed to identify the location of OF in FCB Grid by testing the sequencing of Knowledge, Attitude and Purchase Behavior effects. Two scales were adopted from a study by Ghosh et al. (2016 ) to measure Knowledge and Attitude pertaining to organic food. Similar such scale with minor moderation was formed for Purchase behavior. 868 responses were analyzed through Structural Equation Model, which indicates that OF falls on the first quadrant of FCB grid and is a high involvement product. This implies Knowledge drives Attitude and Attitude drives Purchase Behavior and demands informative strategy where economic considerations prevail prior to purchase. Organic food production is a sustainable process and positively impacts the livelihood of marginal farmers and will improve the quality of the soil and health of the consumers.